If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3(3x + -8) = 4(3x + -9) + 6x Reorder the terms: 5x + -3(-8 + 3x) = 4(3x + -9) + 6x 5x + (-8 * -3 + 3x * -3) = 4(3x + -9) + 6x 5x + (24 + -9x) = 4(3x + -9) + 6x Reorder the terms: 24 + 5x + -9x = 4(3x + -9) + 6x Combine like terms: 5x + -9x = -4x 24 + -4x = 4(3x + -9) + 6x Reorder the terms: 24 + -4x = 4(-9 + 3x) + 6x 24 + -4x = (-9 * 4 + 3x * 4) + 6x 24 + -4x = (-36 + 12x) + 6x Combine like terms: 12x + 6x = 18x 24 + -4x = -36 + 18x Solving 24 + -4x = -36 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 24 + -4x + -18x = -36 + 18x + -18x Combine like terms: -4x + -18x = -22x 24 + -22x = -36 + 18x + -18x Combine like terms: 18x + -18x = 0 24 + -22x = -36 + 0 24 + -22x = -36 Add '-24' to each side of the equation. 24 + -24 + -22x = -36 + -24 Combine like terms: 24 + -24 = 0 0 + -22x = -36 + -24 -22x = -36 + -24 Combine like terms: -36 + -24 = -60 -22x = -60 Divide each side by '-22'. x = 2.727272727 Simplifying x = 2.727272727
| 3(8x+2)=5x | | 36=-7x+12-c | | 6m+6=41 | | 9+7=16 | | -5+6=36 | | 5x-12x-7=108 | | 9x^2-9xy+2y^2=0 | | 9-9x=-18 | | 6-4r=7(6+2r) | | 8-8(x-4)=6x | | 6x-1=9x+8 | | -5-8n-3n=4-8n | | 6r-2t+5r+t= | | 16=-6n-2n | | x(2x-3)=0 | | 39*(5v)=325 | | 7-2(x-8)=3x-(4-x) | | x+4+1(x-3)=7 | | a+b*4=c | | 8(v+5)=-16-6v | | -3.5=-2.5 | | -4m+8m-6=-3m+6m | | -147=-7(1+5n) | | 135m=225 | | -(3x-2)-(7x-7)+4=-7(x-4)-(6x+7)+2 | | x+4+1=7 | | 10=7m | | 3x^2-33x-36=0 | | -6(1+7n)+7(1+6n)=-2 | | c/7-12=-4 | | x^2+7x=-3x-25 | | 5--1+(-4)= |